Influência das atividades antrópicas sobre a colonização em substrato artificial por macroinvertebrados bentônicos em rio de baixa ordem no Sul do Brasil - Fitarelli, Bruna (2017)
Assuming the presumption that the anthropic impacts influence benthic macroinvertebrates, this study aimed to verify, through the analysis of the colonization by benthic macroinvertebrates in the artificial substrate, possible influences of different degrees of impact on the attributes of community, colonization And ecological succession and composition of functional trophic groups. Specifically, this study sought to answer the following questions: i) will there be changes in community attributes and functional groups at the sampling points and over the exposure period of the artificial substrates? Ii) Does the degree of impact influence the process of colonization and ecological succession and the distribution of functional trophic groups? Samples were collected in the Toledo river (Toledo-PR) between March and May 2016 at three sampling points distributed in the nascent-foz direction (P1 – Nascente, P2 - Meio and P3 – Foz). It was verified the colonization of 2,019 individuals (ind) being the highest occurrence of Chironomidae (1044 ind) followed by Oligochaeta (475 ind) and Glossiphoniidae (347 ind). Although the equitability had lower values temporarily in P3, the community attributes did not have significant influence, both in the points as in the exposure period of the substrate. In relation to the distribution of the taxa temporally and spatially, it was possible to observe a process of ecological succession mainly in the points with the lowest degree of impact and, together with the higher occurrences of tolerant species in P3, indicates an influence of the environmental degradation on the distribution of the taxa . However, the distribution of the functional trophic groups did not show any influence on the time of exposure of the substrate, but in relation to the collection points, the degree of impact may have influenced the occurrences, since it changed the proportion of the occurrence of these groups, due to the increase of Organisms belonging to tolerant groups.